Sitting or Standing in VR: About Comfort, Conflicts, and Hazards - Zielasko, Daniel; Riecke, Bernhard E. (IEEE Computer Graphics and Applications, 2024)
This article examines the choices between sitting and standing in virtual reality (VR) experiences, addressing conflicts, challenges, and opportunities. It explores issues such as the risk of motion sickness in stationary users and virtual rotations, the formation of mental models, consistent authoring, affordances, and the integration of embodied interfaces for enhanced interactions. Furthermore, it delves into the significance of multisensory integration and the impact of postural mismatches on immersion and acceptance in VR. Ultimately, the article underscores the importance of aligning postural choices and embodied interfaces with the goals of VR applications, be it for entertainment or simulation, to enhance user experiences.
Keywords: Behavioral sciences; Cognitive science; Motion sickness; Multisensory integration; NSERC DG 2026; Riecke; Riecke_2024; User experience; Virtual reality; bernhard-riecke; daniel-zielasko; journalPaper